2020
DOI: 10.1007/s13201-020-01271-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of persulfate-based advanced oxidation process (US/PS/Fe3O4) for ciprofloxacin removal from aqueous solutions

Abstract: Research evidence has shown that pollution of surface and underground waters is the leading sources of environmental and health-related problems. Disposed unused therapeutic drugs have been known to contaminate underground water and also offer drug resistance to infection-causing bacterial. This research seeks to evaluate the use of US/PS/Fe 3 O 4 for the removal of ciprofloxacin (CIP-F) from aqueous solutions. The research also seeks to obtain the optimum set of conditions about which the highest removal effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…Có nhiều phương pháp để loại bỏ các chất màu nói chung và MB ra khỏi nguồn nước như phương pháp oxi hóa [2], phương pháp hóa học [3], phương pháp sinh học [4] nhưng phương pháp hấp phụ được nhiều nghiên cứu lựa chọn bởi chi phí xử lý thấp, hiệu quả cao, công nghệ đơn giản [5][6][7][8][9]. Cho đến nay, rất nhiều các chất hấp phụ đã được sử dụng để loại bỏ MB ra khỏi môi trường nước như CNTs [8], các oxit kim loại [10], vỏ trấu [11], mùn cưa [12], … Tuy nhiên các chất này có dung lượng hấp phụ thấp, thời gian hấp phụ kéo dài.…”
Section: Giới Thiệu Chungunclassified
“…Có nhiều phương pháp để loại bỏ các chất màu nói chung và MB ra khỏi nguồn nước như phương pháp oxi hóa [2], phương pháp hóa học [3], phương pháp sinh học [4] nhưng phương pháp hấp phụ được nhiều nghiên cứu lựa chọn bởi chi phí xử lý thấp, hiệu quả cao, công nghệ đơn giản [5][6][7][8][9]. Cho đến nay, rất nhiều các chất hấp phụ đã được sử dụng để loại bỏ MB ra khỏi môi trường nước như CNTs [8], các oxit kim loại [10], vỏ trấu [11], mùn cưa [12], … Tuy nhiên các chất này có dung lượng hấp phụ thấp, thời gian hấp phụ kéo dài.…”
Section: Giới Thiệu Chungunclassified
“…A study by Olufemi and Bolanle (2018) on the examination of the international portfolio diversification of the Nigeria Stock Market concluded that the Nigerian stock market has suffered from the shocks of crises. Based on such findings, Ahmadi et al (2020) pointed out that the stock market is safe for investors before the COVID-19 crises, but in these times, COVID-19 has made it difficult to invest.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The COVID-19 pandemic which has affected many, resulting in deaths had also greatly impacted the stock exchange market all over the world. A study by Ahmadi et al (2020) on the effects of COVID-19 outbreak on the Nigerian stock exchange performance pointed out that there is a loss in stock returns. It was further revealed that the returns on stocks have seen high levels of volatility under the period of COVID-19.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The removal % of Pb (II) using Kaolinite/Smectite reached 75 % at 120 min. In [42], indicated that US/PS/Fe 3 O 4 process can effectively and efficiently aid the surface adsorption of CIP-F from aqueous solutions with 98.3% of removal efficiency percentage at pH = 5, CIP-F concentration= 200 mg/L, PS concentration = 0.15 mol/L and Fe 3 O 4 concentration = 0.01 g/L at a resident time of 45 min.…”
Section: Introductionmentioning
confidence: 97%